Home visits to improve breast health knowledge and screening practices in a less privileged area in Jordan - Taha, Hana (BioMed Central, 2014)
BACKGROUND: Breast cancer is the most common cancer afflicting women in Jordan. This study aimed to assess the effects of an educational intervention through home visits, including offering free mammography screening vouchers, on changing women’s breast health knowledge and screening practices for early detection of breast cancer in a less privileged area in Jordan. METHODS: Two thousand four hundred breast health awareness home visits were conducted and 2363 women aged 20-79 years (median: 41) answered a pre-test interview-administrated questionnaire to assess their breast health knowledge and practices at the baseline. After a home-based educational session, 625 women aged 40 years or older were referred to free mammography screening. Five hundred and ninety six homes were revisited six months later and out of these 593 women participated in a post-test. The women’s retained breast health knowledge, the changes in their reported breast health practices and their usage of the free mammography voucher, were assessed. RESULTS: The mean knowledge score increased significantly (p < 0.001) from 11.4 in the pre-test to 15.7 in the post-test (maximum score: 16). At the six month follow-up the post-test showed significant (p < 0.001) improvement in women’s perceived breast self-examination (BSE) knowledge, reported BSE practice and mammography screening. Out of 625 women that received a voucher for free mammography screening 73% attended the mammography unit, while only two women without a voucher went for mammography screening at the assigned unit. Women who received a follow-up visit were more likely to use the free mammography voucher compared to those who were not followed-up (83% vs. 67%; p < 0.001). CONCLUSIONS: Home visits by local community outreach workers that incorporated education about breast cancer and breast health in addition to offering free mammography screening vouchers were effective in improving women’s breast health knowledge and practices in a less privileged area in Jordan.